Prevalence of Vitamin D and Calcium Deficiency among a Sample of People in the Gharyan City, Western Libya - Al Basher Alafi; Ahmed Ashtawa; Marwa Al Mabrok; Abdulali Taweel; Reema Mohammed; Siddig Bushra (AlQalam Journal of Medical and Applied Sciences, 2026)
The study aimed to determine the prevalence of vitamin D and calcium deficiency in a sample of residents in the city of Gharyan, located in the western regions of Libya, based on 300 cases visiting laboratories and clinics and medical clinics in the city for the year 2025 AD, divided into two groups for both sexes with a number of (150) cases, for different age groups from (5-85) years The study reached results showing that vitamin D and calcium deficiency is widespread among cases for both sexes, as the percentage of vitamin D deficiency in males reached 29.34%, and in females it reached 25.66%, calcium deficiency was recorded at 25.34% in males and 24.66% in females. The highest prevalence of vitamin deficiency was recorded in the age group of (46-65) years, at 20.66% in males, and 25.33% in females. Followed by the age group from (26-45) years, with 29% of the total cases, 14.33% in males, and 14.66% in females. This is consistent with many studies conducted in some areas of the entire country, which confirmed that most of the population and different age groups suffer from a deficiency in the level of vitamin D and calcium, despite the country’s location in an environmental zone suitable for the availability of sufficient sunlight However, due to some reasons of lack of health awareness, daily lifestyle and some social and dietary habits that have further exacerbated the problem of the spread of vitamin D and calcium deficiency among the population, the study recommended conducting intensive research and studies in various regions and following up on the cases of the population, spreading health awareness through various available means and holding scientific seminars and conferences for specialists, to educate society about the dangers of vitamin D and calcium deficiency on public health Changing habits and daily life patterns, conducting routine examinations, and following a healthy diet to reduce the increasing shortage rates among different age groups of the population.